High temperature resistant interior hot melt adhesive and preparation method thereof
By performing chain extension reactions based on polyamide and isocyanate and capping with hydroxysilane, forming a PA-PU copolymer hot melt adhesive, the hardness and water resistance of the existing high-temperature hot melt adhesive in the automotive interior field is solved. Insufficient problems, hot melt adhesive products with high heat resistance and water resistance are achieved.
Patent Information
- Application Number
- CN202411455088.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-18
AI Technical Summary
The application of existing high-temperature resistant hot melt adhesives in the automotive interior field is limited by their high melting point, hardness and poor water resistance, and it is difficult to meet the needs of higher heat and water resistance.
By chain-extending reaction of polyamide with isocyanate and capping and crosslinking with hydroxysilane, a new PA-PU copolymer hot melt adhesive is formed, reducing hardness and melting point, while improving thermal stability and water resistance. A hot melt adhesive with high temperature resistant interior is prepared.
The heat resistance of hot melt adhesive is achieved exceeding 150℃, and maintains stability above 200℃, and has good water resistance and easy processing. It is suitable for automotive interior bonding.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of hot melt adhesives, and in particular to a high temperature resistant interior decoration hot melt adhesive and a preparation method thereof. Background Art
[0002] Hot melt adhesive is widely used in industrial production, such as textile, packaging, electronics, automobile and other industries. According to the temperature resistance, it is divided into ordinary hot melt adhesive and high temperature resistant hot melt adhesive. The high temperature resistance range of ordinary hot melt adhesive is usually 70-80℃, while the high temperature resistance range of high temperature resistant hot melt adhesive can reach above 100℃.
[0003] High temperature resistant hot melt adhesives mainly include polyamide (PA) hot melt adhesive, polyethersulfone (PES) hot melt adhesive, thermoplastic polyurethane elastomer (TPU) hot melt adhesive and ethylene vinyl acetate copolymer (EVA) hot melt adhesive, etc. Among them, PA hot melt adhesive has a significant feature compared with other thermoplastic resins, that is, when it is heated and cooled, the melting and solidification of the resin occur in a narrow temperature range; this feature enables PA hot melt adhesive to solidify quickly after heating, melting and coating and slightly cooling during construction; it also enables it to have good bonding properties at temperatures close to the softening point.
[0004] In addition, since the adhesion of PA hot melt adhesive is related to its softening point, the high temperature resistance of different products can be adjusted by adjusting the polymerization formula or process parameters. The high temperature resistance of some PA hot melt adhesives can reach above 150°C. They are widely used in the automotive industry, especially in the field of automotive interior bonding. Currently, PA hot melt adhesive is mainly used. However, most PA hot melt adhesives have high melting points and hardness, and poor water resistance, so they are subject to certain restrictions in use and need to be improved. Summary of the invention
[0005] The purpose of the present invention is to solve the shortcomings of the prior art and to propose a high temperature resistant interior decoration hot melt adhesive and a preparation method thereof.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] A high temperature resistant interior hot melt adhesive is prepared by mixing and reacting at least the following components in weight percentage:
[0008] 65.8wt%-67.0wt% polyamide, specifically amine-terminated polyamide;
[0009] 21.9wt%-22.3wt% polyurethane, specifically isocyanate-terminated polyurethane;
[0010] 10.7wt%-12.3wt% of hydroxysilane, namely silane 3-aminopropyltrihydroxysilane, reacts with excess isocyanate groups.
[0011] The present invention also provides a method for preparing the aforementioned high temperature resistant interior hot melt adhesive, comprising the following steps:
[0012] S1. Preparation of polyamide melt
[0013] Add 5.12 kg of 1,12-dodecanediamine (aqueous solution with a solute content of 99.0 wt%), 2.03 kg of 2,2,4-trimethylhexamethylenediamine, 4.14 kg of dimer acid, 1.20 kg of sebacic acid, 1.5 g of hypophosphorous acid aqueous solution (with a solute content of 50 wt%), and 7 kg of deionized water into the reactor, melt at 130 ° C, replace with nitrogen to 0.2 MPa, then heat to 180 ° C, react for 2 hours to obtain a polyamide melt, and dry for later use;
[0014] S2. Preparation of polyurethane
[0015] Diisocyanate, diol and butanetriol are added in a molar ratio of 1.3-1.38:1:0.12, heated to 80°C, and triethanolamine is added in an amount of 5% by weight of the diol. The mixture is stirred and reacted for 30 minutes until the viscosity of the system increases to 1000-1200 cPa·s. The mixture is cooled to obtain a polyurethane system in a solution state for standby use;
[0016] S3, melt mixing reaction
[0017] The polyurethane system and 2,2,4-trimethylhexamethylenediamine are mixed in a weight ratio of 100:2-3 to obtain a drop liquid, which is immediately ready for use;
[0018] Under nitrogen protection, the polyamide melt after S1 drying was softened at 160°C for 30 min, and then stirred at 1000 r / min to break it into fluffy silk balls, and then dripping liquid was added continuously, and the dripping liquid was added within 15 min.
[0019] The temperature was raised to 180°C and the pressure was increased to 0.6 MPa. The melt was subjected to nitrogen jet impact and stirred for 30 minutes to obtain a mixed melt.
[0020] S4, Silane Termination Reaction
[0021] At 180°C and 1.2-1.5MPa, 3-aminopropyltrihydroxysilane was added to the mixed melt, and after nitrogen jet impact, the mixture was stirred and reacted for 30 minutes, and the hot melt adhesive product was obtained after cooling.
[0022] Preferably, the polyamide melt in the S1 reaction has a COOH terminal group content of 55 mmol / kg and an NH2 terminal group content of 384 mmol / kg, indicating that the polyamide chain is terminated with NH2.
[0023] Preferably, after the S1 reaction, the internal pressure of the reactor is detected to be 0.27-0.32 MPa, at which time the discharge valve is quickly opened, and the polyamide melt is automatically ejected under the action of the internal pressure, and a rotating disk is used to receive the material to obtain a soft and transparent spiral melt.
[0024] Preferably, the soft and transparent spiral melt is dried at 110° C. under nitrogen for 24 hours, and the water content is detected to be less than 0.2%, thereby obtaining a slightly hardened polyamide melt.
[0025] Preferably, in S2, the molar ratio of 2,2,4-trimethylhexamethylene diisocyanate to 1,6-hexamethylene diisocyanate in the diisocyanate is 4:1, and the molar ratio of hexanediol to 3-methyl-1,5-pentanediol in the diol is 3:1.
[0026] Preferably, the weight ratio of the polyamide melt to the dripping liquid in S3 is 3:1.
[0027] Preferably, in S3, the pressure of the nitrogen gas injection is 2 MPa, the nitrogen pipe is inclined downward at 45° along the side wall of the reactor and stirring is maintained, and when the internal pressure of the reactor exceeds 2 MPa, the pressure relief valve is opened for immediate pressure reduction.
[0028] Preferably, the weight ratio of the mixed melt to 3-aminopropyltrihydroxysilane in S4 is 10:1.3±0.1. 3-aminopropyltrihydroxysilane has both primary amine groups and silanol groups, reacts relatively quickly with isocyanate groups, has a capping effect, and cross-links to increase the viscosity of the system, thereby improving thermal stability and water resistance.
[0029] Preferably, after the S4 reaction, the internal pressure of the reactor is detected to be 1.4-1.5MPa. At this time, the discharge valve is quickly opened, and the mixed melt is automatically ejected and extruded under the action of the internal pressure. A receiving barrel is used to receive the material to obtain a coil-like fiber solid. After cooling, it is sheared and crushed to obtain a powdered hot melt adhesive product. When in use, it is added to a hot melt gun for heating, extrusion and bonding.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The invention prepares a polyamide which is resistant to high temperature of more than 150°C and is terminated by amino groups, carries out a chain extension reaction with a polyurethane terminated by isocyanate, and finally consumes and crosslinks the redundant terminated or free isocyanate groups by hydroxyl silane, and mixes two commonly used hot melt adhesive materials which are difficult to mix, namely, polyurethane (referring to a linear thermoplastic elastomer) and polyamide, through a melt mixing reaction mode, so that a high-viscosity melt and a low-viscosity solution are mixed and reacted to generate a PA-PU copolymer, and then terminated by hydroxyl silane and a polyurethane with a flexible chain is used to reduce the hardness and the melting point, and obtain a new type of hot melt adhesive product which is heat-resistant above 150°C (referring to the softening of the hot melt adhesive, and the actual heat resistance stability is more than 200°C), water-resistant and easy to be processed into adhesive bonding, and the product is easy to spread on the surface of a metal or plastic substrate when hot-melted, is difficult to crystallize and has high stability.
[0032] Since polyurethane is used, carbodiimide cross-linking agents and the like can be added to the product of the present invention to improve the bonding effect, further improve the bonding stability, and avoid the defect that the urethane bond of pure polyurethane hot melt adhesive is unstable at the application temperature. Therefore, the product of the present invention has the advantages of both polyurethane hot melt adhesive and polyamide hot melt adhesive. DETAILED DESCRIPTION
[0033] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments.
[0034] Preparation Example 1:
[0035] Preparation of polyamide melt: add 5.12 kg of 1,12-dodecanediamine (aqueous solution with solute accounting for 99.0 wt%), 2.03 kg of 2,2,4-trimethylhexamethylenediamine, 4.14 kg of dimer acid, 1.20 kg of sebacic acid, 1.5 g of hypophosphorous acid aqueous solution (solute accounting for 50 wt%), and 7 kg of deionized water into a reactor, melt at 130 ° C, replace with nitrogen to 0.2 MPa, then heat to 180 ° C, react for 2 hours to obtain a polyamide melt, and dry for use;
[0036] Among them, the content of COOH terminal groups in the polyamide melt was 55mmol / kg, and the content of NH2 terminal groups was 384mmol / kg, proving that it was an NH2-terminated polyamide chain;
[0037] After the reaction, the internal pressure of the reactor is detected to be 0.27-0.32MPa. At this time, the discharge valve is quickly opened. Under the action of the internal pressure, the polyamide melt is automatically ejected, and a rotating disk is used to receive the material to obtain a soft and transparent spiral melt.
[0038] The soft and transparent spiral melt is dried at 110° C. under nitrogen for 24 hours, and the water content is detected to be less than 0.2%, thereby obtaining a slightly hardened polyamide melt.
[0039] Preparation Example 2:
[0040] Preparation of polyurethane: diisocyanate, diol and butanetriol were added in a molar ratio of 1.3:1:0.12, heated to 80°C, and triethanolamine was added at 5% by weight of diol. The mixture was stirred and reacted for 30 minutes until the viscosity of the system increased to 1000-1200 cPa·s. The polyurethane system was cooled to obtain a solution for standby use;
[0041] The polyurethane system and 2,2,4-trimethylhexamethylenediamine are mixed at a weight ratio of 100:2 to obtain a drop liquid, which is immediately ready for use;
[0042] The molar ratio of 2,2,4-trimethylhexamethylene diisocyanate to 1,6-hexamethylene diisocyanate in the diisocyanate is 4:1, and the molar ratio of hexanediol to 3-methyl-1,5-pentanediol in the diol is 3:1.
[0043] Preparation Example 3:
[0044] Preparation of polyurethane: diisocyanate, diol and butanetriol were added in a molar ratio of 1.35:1:0.12, heated to 80°C, and triethanolamine was added at 5% by weight of diol. The mixture was stirred and reacted for 30 minutes until the viscosity of the system increased to 1000-1200 cPa·s. The polyurethane system was cooled to obtain a solution for standby use;
[0045] The polyurethane system and 2,2,4-trimethylhexamethylenediamine are mixed in a weight ratio of 100:3 to obtain a drop liquid, which is immediately ready for use;
[0046] The molar ratio of 2,2,4-trimethylhexamethylene diisocyanate to 1,6-hexamethylene diisocyanate in the diisocyanate is 4:1, and the molar ratio of hexanediol to 3-methyl-1,5-pentanediol in the diol is 3:1.
[0047] Preparation Example 4:
[0048] Preparation of polyurethane: diisocyanate, diol and butanetriol were added in a molar ratio of 1.38:1:0.12, heated to 80°C, and triethanolamine was added at 5% by weight of diol. The mixture was stirred and reacted for 30 minutes until the viscosity of the system increased to 1000-1200 cPa·s. The polyurethane system was cooled to obtain a solution for standby use;
[0049] The polyurethane system and 2,2,4-trimethylhexamethylenediamine are mixed in a weight ratio of 100:2.5 to obtain a drop liquid, which is immediately ready for use;
[0050] The molar ratio of 2,2,4-trimethylhexamethylene diisocyanate to 1,6-hexamethylene diisocyanate in the diisocyanate is 4:1, and the molar ratio of hexanediol to 3-methyl-1,5-pentanediol in the diol is 3:1.
[0051] Comparative Preparation Example 1:
[0052] Preparation of polyurethane: diisocyanate and diol are added in a molar ratio of 1.38:1.18, heated to 80°C, and triethanolamine is added in an amount of 5% by weight of the diol. The mixture is stirred and reacted for 30 minutes until the viscosity of the system increases to 1000-1200 cPa·s. The polyurethane system is cooled to obtain a solution for standby use;
[0053] The polyurethane system and 2,2,4-trimethylhexamethylenediamine are mixed in a weight ratio of 100:2.5 to obtain a drop liquid, which is immediately ready for use;
[0054] The molar ratio of 2,2,4-trimethylhexamethylene diisocyanate to 1,6-hexamethylene diisocyanate in the diisocyanate is 4:1, and the molar ratio of hexanediol to 3-methyl-1,5-pentanediol in the diol is 3:1.
[0055] Comparative Preparation Example 2:
[0056] Preparation of polyurethane: diisocyanate, diol and butanetriol were added in a molar ratio of 1.38:1:0.12, heated to 80°C, and triethanolamine was added at 5% by weight of the diol. The mixture was stirred and reacted for 30 minutes until the viscosity of the system increased to 1000-1200 cPa·s. The polyurethane system was cooled to obtain a solution. No 2,2,4-trimethylhexamethylenediamine was added, and the solution was directly used as a drop liquid for immediate use.
[0057] The molar ratio of 2,2,4-trimethylhexamethylene diisocyanate to 1,6-hexamethylene diisocyanate in the diisocyanate is 4:1, and the molar ratio of hexanediol to 3-methyl-1,5-pentanediol in the diol is 3:1.
[0058] Embodiment 1:
[0059] A method for preparing a high temperature resistant interior hot melt adhesive comprises the following steps:
[0060] Under nitrogen protection, the dried polyamide melt obtained in Preparation Example 1 was placed at 160° C. to soften for 30 min, and then stirred at 1000 r / min to break it into a fluffy silk ball, and then the droplets of Preparation Example 2 were added. The droplets were added within 15 min, and the weight ratio of the polyamide melt to the droplets was 3:1.
[0061] The temperature was raised to 180°C and the pressure was increased to 0.6 MPa. The melt was subjected to nitrogen jet impact and stirred for 30 minutes to obtain a mixed melt.
[0062] The pressure of nitrogen gas injection is 2MPa, and the nitrogen pipe is tilted downward at 45° along the side wall of the reactor, and stirring is maintained. When the pressure inside the reactor exceeds 2MPa, the pressure relief valve is opened to immediately reduce the pressure.
[0063] The weight ratio of the mixed melt to 3-aminopropyltrihydroxysilane is 10:1.3±0.1. 3-aminopropyltrihydroxysilane has both primary amine groups and silanol groups, reacts rapidly with isocyanate groups, has a capping effect, and cross-links to increase the viscosity of the system, thereby improving thermal stability and water resistance.
[0064] At 180℃ and 1.2-1.5MPa, 3-aminopropyltrihydroxysilane is added to the mixed melt, and after nitrogen jet impact, the mixture is stirred for 30 minutes. After the reaction, the internal pressure of the reactor is detected to be 1.4-1.5MPa. At this time, the discharge valve is quickly opened. Under the action of the internal pressure, the mixed melt is automatically ejected and extruded. The material is received in a receiving barrel to obtain a coil-like fiber solid. After cooling, it is sheared and crushed to obtain a powdered hot melt adhesive product. When in use, it is added to a hot melt gun for heating, extrusion and bonding.
[0065] Embodiment 2:
[0066] Basically the same as Example 1, except that the droplets are prepared in Preparation Example 3.
[0067] Embodiment 3:
[0068] It is basically the same as Example 1, except that the droplets are prepared in Preparation Example 4.
[0069] Comparative Example 1:
[0070] It is basically the same as Example 1, except that the droplet is prepared by Comparative Preparation Example 1.
[0071] Comparative Example 2:
[0072] It is basically the same as Example 1, except that the droplet is prepared by Comparative Preparation Example 2.
[0073] List of medicines:
[0074] Dimer acid (i.e. dimer fatty acid, C 36 H 68 O4 molecular weight: 564.9227, Nantong Runfeng Petrochemical Co., Ltd.), 3-aminopropyl trihydroxysilane isocyanate (Shanghai MacLean Biochemical Technology Co., Ltd.), 2,2,4-trimethylhexamethylenediamine (Shanghai Xianding Biotechnology Co., Ltd.), and the rest were purchased from Aladdin.
[0075] The resulting product:
[0076] A high temperature resistant interior hot melt adhesive is prepared by mixing and reacting at least the following components in weight percentage:
[0077] 65.8wt%-67.0wt% polyamide, specifically amine-terminated polyamide;
[0078] 21.9wt%-22.3wt% polyurethane, specifically isocyanate-terminated polyurethane;
[0079] 10.7wt%-12.3wt% of hydroxysilane, namely silane 3-aminopropyltrihydroxysilane, reacts with excess isocyanate groups.
[0080] Performance Test:
[0081] The performance of the hot melt adhesive products of Examples 1-3 and Comparative Examples 1-2 was tested according to the T / SHPTA 069-2023 "Reactive Polyurethane Hot Melt Adhesive for Automotive Interiors" issued by the Chinese Group Standard. The specific testing process is as follows:
[0082] 1) Hot pressing and fixing: Spread the powder of each hot melt adhesive product between two substrates (one is a silicon wafer and the other is a PVC plastic sheet) with a thickness of 0.35±0.03mm, and perform hot pressing at a temperature of 170-180℃ and a pressure of 10-50kg / cm 2 , hot pressing time is 20-50s;
[0083] 2) Adhesion test: Prepare a 10mm×3mm test piece and test it at a pulling speed of 200MM / min;
[0084] 3) Viscosity test: Use a dynamic mechanical analyzer to measure the viscosity at 120℃, 150℃, 180℃, and 200℃ respectively, observe the viscosity changes, and thus verify the construction conditions.
[0085] 4) Water absorption test: Place the test piece in an environment of 50°C and 100% humidity. After wiping off the surface moisture, the wet weight is obtained. Water absorption = (wet weight - dry weight) / dry weight. The test results are shown in Table 1.
[0086] Table 1. Hot melt adhesive adhesion, heat resistance and water resistance test
[0087]
[0088] As shown in Table 1, butanetriol crosslinking and diamine chain extension have a great influence on the polyurethane reaction, especially on the subsequent adhesion (adhesion), and the temperature test shows that the product of the present invention can be used for a long time at about 150°C (i.e., temperature near the softening point). This product is still a primary product without adding a curing crosslinking agent. It can be expected that after adding a carbodiimide crosslinking agent, it will bring about a crosslinking curing effect, that is, convert the non-reactive molding of this product into reactive molding, and the application range of this product is wider (improving the temperature resistance of thermosetting).
[0089] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing a high temperature resistant interior hot melt adhesive, characterized in that: The following steps are involved: S1. Preparation of polyamide melt Add 5.12 kg of 1,12-dodecanediamine, 2.03 kg of 2,2,4-trimethylhexamethylenediamine, 4.14 kg of dimer acid, 1.20 kg of sebacic acid, 1.5 g of hypophosphorous acid aqueous solution, and 7 kg of deionized water into the reactor, melt at 130°C, replace with nitrogen to 0.2 MPa, then heat to 180°C, react for 2 hours to obtain a polyamide melt, and dry for later use; S2. Preparation of polyurethane Diisocyanate, diol and butanetriol are added in a molar ratio of 1.3-1.38:1:0.12, heated to 80°C, and triethanolamine accounting for 5% of the weight of the diol is added, stirred and reacted for 30 minutes until the viscosity of the system increases to 1000-1200 cPa·s, and cooled to obtain a solution-like polyurethane system for standby use; wherein the molar ratio of 2,2,4-trimethylhexamethylene diisocyanate and 1,6-hexamethylene diisocyanate in the diisocyanate is 4:1, and the molar ratio of hexanediol and 3-methyl-1,5-pentanediol in the diol is 3:1; S3, melt mixing reaction The polyurethane system and 2,2,4-trimethylhexamethylenediamine are mixed in a weight ratio of 100:2-3 to obtain a drop liquid, which is immediately ready for use; Under nitrogen protection, the polyamide melt after S1 drying was softened at 160°C for 30 min, and then stirred at 1000 r / min to break it into a fluffy silk ball, and then dripping liquid was added continuously. The weight ratio of polyamide melt to dripping liquid was 3:1, and the dripping liquid was added within 15 min. The temperature was raised to 180°C and the pressure was increased to 0.6 MPa. The melt was subjected to nitrogen jet impact and stirred for 30 minutes to obtain a mixed melt. S4, Silane Termination Reaction At 180°C and 1.2-1.5MPa, 3-aminopropyltrihydroxysilane was added to the mixed melt, the weight ratio of the mixed melt to 3-aminopropyltrihydroxysilane was 10:1.3±0.1, and the mixture was subjected to nitrogen jet impact, stirred and reacted for 30 minutes, and cooled to obtain a hot melt adhesive product.
2. The method for preparing a high temperature resistant interior hot melt adhesive according to claim 1, characterized in that: The polyamide melt from the S1 reaction has a COOH terminal group content of 55 mmol / kg and an NH2 terminal group content of 384 mmol / kg.
3. The method for preparing a high temperature resistant interior hot melt adhesive according to claim 1, characterized in that: After the S1 reaction, the internal pressure of the reactor is detected to be 0.27-0.32 MPa. At this time, the discharge valve is quickly opened. Under the action of the internal pressure, the polyamide melt is automatically ejected and a rotating disk is used to receive the material to obtain a soft and transparent spiral melt.
4. The method for preparing a high temperature resistant interior hot melt adhesive according to claim 3, characterized in that: The soft and transparent spiral melt is dried at 110° C. under nitrogen for 24 hours, and the water content is detected to be less than 0.2%, thereby obtaining a polyamide melt.
5. The method for preparing a high temperature resistant interior hot melt adhesive according to claim 1, characterized in that: In S3, the pressure of the nitrogen gas injection is 2 MPa, and the nitrogen pipe is inclined downward at 45° along the side wall of the reactor and kept stirring. When the internal pressure of the reactor exceeds 2 MPa, the pressure relief valve is opened to immediately reduce the pressure.
6. The method for preparing a high temperature resistant interior hot melt adhesive according to claim 1, characterized in that: After the S4 reaction, the internal pressure of the reactor is detected to be 1.4-1.5MPa. At this time, the discharge valve is quickly opened. Under the action of the internal pressure, the mixed melt is automatically ejected and extruded. A receiving barrel is used to receive the material to obtain a coil-like fiber solid. After cooling, it is sheared and crushed to obtain a powdered hot melt adhesive product. When in use, it is added to a hot melt gun for heating, extrusion and bonding.
